Uv curable coatings with high refractive index
By using a coating composition containing metal oxide nanoparticles and specific monomers, combined with UV-Vis curing technology, the problem of difficulty in producing a high refractive index coating in thick layers in the prior art is solved, and excellent chemical, mechanical and light resistance characteristics are achieved.
Patent Information
- Application Number
- CN202380053129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-05
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has difficulty in producing coatings with high refractive index, excellent chemical and mechanical stability, and excellent light resistance in thick layers, especially in terms of cost and performance.
Coating compositions are employed that include single or mixed metal oxide nanoparticles, monomers with at least three thiol groups at the end and optionally monomers with specific functional groups. The composition forms a high refractive index crosslinked coating by UV-Vis curing technique.
The formation of coatings with high refractive index and excellent chemical, mechanical and light resistance characteristics at relatively low UV doses is achieved, and is suitable for the manufacture of light output coupling layers for optical waveguides, solar panels, display and lighting devices, and anti-reflective coatings.
Smart Images

Figure BDA0005236835150000022 
Figure BDA0005236835150000201 
Figure BDA0005236835150000202
Abstract
Description
[0001] The present invention relates to a coating composition comprising i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm; ii) one or more monomers having at least three thiol groups (-SH) at the terminal (first monomer), and
[0002] iii) optionally one or more monomers having at least two functional groups at the terminal ends capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer),
[0003] iv) one or more solvents; coatings obtained therefrom and the use of these compositions for coating surface relief micro- and nanostructures (e.g. holograms), manufacturing optical waveguides, solar panels, light outcoupling layers for display and lighting devices, and antireflection coatings. The coating obtained from the coating composition has a high refractive index, and when the coating composition is applied to a hologram, the hologram is bright and visible from any angle. Background Art
[0004] JP 2020029542A (US2020 / 062927) relates to an organic-inorganic composite composition comprising a polymer (A) having a triazine ring structure in a polymer main chain structure; inorganic fine particles (B); and a The surface treatment agent (C) of the present invention, wherein the inorganic fine particles (B) have a number base median size (D) of 1 nm or more and 20 nm or less. n50 ), and R1 is a carboxyl group, a phosphate group, a sulfonyl group, or an alkyl group, an alkenyl group, an alkynyl group, an aryl group, an aralkyl group, or an amino group (all of which are optionally substituted); molded articles and optical components comprising the organic-inorganic composite composition.
[0005] US10717866B2 (US2018 / 0244915) relates to an organic-inorganic hybrid composition comprising a polymer (A) comprising a triazine ring structure represented by the general formula (1) in the polymer backbone structure:
[0006] Wherein, in the formula, R1 is a substituted or unsubstituted alkyl, aryl, aralkyl, amino, arylamino, alkylthio, or arylthio;
[0007] Inorganic fine particles (B); and
[0008] a surface treatment agent (C) containing an acidic functional group,
[0009] wherein polymer (A) is a thermoplastic polymer having a glass transition temperature (Tg),
[0010] The number median diameter (D) of inorganic particles (B) n50 ) is greater than or equal to about 1 nm and less than or equal to about 20 nm; and articles and optical components comprising the organic-inorganic hybrid composition.
[0011] US11312840B2 relates to an organic-inorganic hybrid composition comprising:
[0012] A polymer (A) having a triazine ring structure in the main chain of the polymer;
[0013] Inorganic particles (B), such as zirconium oxide, titanium oxide, barium titanate, strontium titanate, zinc oxide, gallium phosphide, cerium oxide, niobium oxide, or a combination thereof; and
[0014] The surface treating agent (C) having a triazine ring structure represented by formula (1):
[0015]
[0016] Wherein, in formula (1), R1 is a carboxyl group, a phosphoric acid group, a sulfonic group, or a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted alkynyl group, a substituted or unsubstituted aryl group, a substituted or unsubstituted aralkyl group, or a substituted or unsubstituted amino group,
[0017] The number median diameter (D) of the inorganic particles (B) n50 ) is greater than or equal to about 1 nanometer and less than or equal to about 20 nanometers,
[0018] in, It is a connection point with adjacent atoms; articles and optical components containing the organic-inorganic hybrid composition.
[0019] US10197820B2 provides quantum dots passivated by oligomers or polymers, which are formed by reacting a first monomer having at least three thiol groups (-SH) at the end with a second monomer, wherein the second monomer has at least two functional groups at the end that can react with the thiol groups and a spacer group between the at least two functional groups.
[0020] US20190338092A1 relates to a flexible color filter and a method for manufacturing the same. An exemplary flexible color filter includes a transparent flexible substrate comprising a thermosetting thiol click polymer.
[0021] US20210403731 relates to a material composition for a light output coupling lens of a quantum dot display panel, the material composition comprising:
[0022] Trimethylolpropane tris(3-mercaptopropionate);
[0023] triethylene glycol divinyl ether; and
[0024] UV free radical initiators;
[0025] The molar ratio of trimethylolpropane tris(3-mercaptopropionate) to triethylene glycol divinyl ether is 2:3, and the material composition is cured by ultraviolet light to form a light output coupling lens, the diameter of the bottom of the light output coupling lens ranges from 30 to 100 microns, and the height of the light output coupling lens ranges from 20 to 80 microns.
[0026] WO 2019 / 016136 discloses surface functionalized titanium dioxide nanoparticles, which are treated with a) a phosphonate of the formula
[0027] or a mixture of phosphonates of formula (I), wherein
[0028] R 1 and R 2 are independently hydrogen, or C1-C4 alkyl,
[0029] R 3 is a group CH2=CH-, or a group of the formula -[CH2] n -R 4 of groups, among which
[0030] n is an integer from 1 to 12,
[0031] When n>3, one -CH2- can be replaced by -S-, provided that S is not directly connected to P, or R 4 ,
[0032] R 4 is hydrogen, or The group,
[0033] R 5 is hydrogen, or C1-C4 alkyl,
[0034] R 6 is hydrogen, or C1-C4 alkyl,
[0035] X 1 is O, or NH, and
[0036] b) with formula R 7 O - (II) and / or
[0037] The alkoxide bonding of
[0038] R 7is a C1-C8 alkyl group which may be interrupted one or more times by -O- and / or substituted one or more times by -OH,
[0039] R 8 is hydrogen, or C1-C4 alkyl,
[0040] R 9 is hydrogen, -CH2OH, -CH2SPh, -CH2OPh, or a compound of formula R 10 -[CH2OH-O-CH2] n1 -group,
[0041] n1 is an integer from 1 to 5,
[0042] X 2 is O, or NH,
[0043] R 10 The formula is -CH2-X 3 -CH2-C(=O)-CR 11 =CH2 group,
[0044] X 3 is O, or NH, and
[0045] R 11 It is hydrogen or C1-C4 alkyl.
[0046] WO 2021 / 052907 relates to a process for preparing single or mixed metal oxide nanoparticles, the process comprising the following steps:
[0047] a) preparing a mixture comprising one or more metal oxide precursor compounds, a solvent, a tertiary alcohol, or a secondary alcohol (wherein the tertiary alcohol and the secondary alcohol eliminate water when the mixture is heated to a temperature above 60° C.), or a mixture containing one or more tertiary alcohols and / or one or more secondary alcohols and optionally water,
[0048] b) heating the mixture to a temperature above 60° C.,
[0049] c) treating the obtained nanoparticles with a base, in particular a base selected from the group consisting of alkali metal alkoxides, alkali metal hydroxides, alkali metal salts of carboxylic acids, tetraalkylammonium hydroxides, trialkylbenzylammonium hydroxides and combinations thereof, wherein
[0050] The one or more metal oxide precursor compounds are selected from the group consisting of: 12 ) x (I) metal alkoxide, formula Me'(Hal) x’ (II) and a metal halide of the formula Me" (Hal') m (OR 12 ')n (III) metal alkoxy halides and mixtures thereof, wherein
[0051] Me, Me' and Me" are independently titanium, tin, tantalum, niobium, hafnium, or zirconium;
[0052] x represents the valence of the metal and is 4 or 5,
[0053] x' represents the valence of the metal and is 4 or 5;
[0054] R 12 and R 12’ are independently C1-C8 alkyl;
[0055] Hal and Hal' are independently Cl, Br or I;
[0056] m is an integer from 1 to 4;
[0057] n is an integer from 1 to 4;
[0058] m+n represents the valence of the metal and is 4 or 5;
[0059] The solvent contains at least one ether group and is different from a tertiary alcohol and a secondary alcohol;
[0060] The ratio of the sum of the moles of hydroxyl groups of the one or more tertiary alcohols and the one or more secondary alcohols to the total moles of Me, Me', and Me" is in the range of 1:2 to 6:1.
[0061] PCT / EP 2021 / 072873 (WO 2022 / 038161) relates to a coating composition comprising i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm; the nanoparticles contain at least one volatile surface-modifying compound selected from alcohols, β-diketones, carboxylic acids and β-ketoesters and mixtures thereof, wherein the total amount of volatile surface-modifying compounds is at least 5% by weight, preferably at least 10% by weight, based on the amount of metal oxide nanoparticles, and ii) a solvent; a coating obtained therefrom and the use of the composition for coating surface relief micro- and nanostructures (e.g., holograms), manufacturing optical waveguides, solar panels, light outcoupling layers for display and lighting devices, and antireflection coatings. The coating obtained from the coating composition has a high refractive index, and when the coating composition is applied to a hologram, the hologram is bright and visible from any angle.
[0062] EP 22159029.2 relates to a composition comprising
[0063] (A) Titanium dioxide nanoparticles,
[0064] (A1) the volume average diameter (Dv50) of the titanium dioxide nanoparticles is in the range of 1 to 10 nm, preferably 1 to 8 nm, more preferably 2 to 6 nm;
[0065] (A2) the titanium dioxide nanoparticles are modified with peroxide groups, and
[0066] (A2) the titanium dioxide nanoparticles optionally comprise a surface modifier selected from the group consisting of phosphates, phosphonates, β-diketones, tertiary amines, carboxylic acids and silanes, or a combination thereof; and
[0067] (B) one or more reactive (free radical polymerizable) diluents, provided that the composition comprises a reactive diluent having at least 2 ethylenically unsaturated groups in the molecule; and
[0068] (C) an organic solvent, and the use of the composition for coating surface relief micro- and nanostructures (such as holograms), manufacturing optical waveguides, solar panels, light output coupling layers for display and lighting devices, and anti-reflection coatings.
[0069] There is a long-standing market need for transparent and colorless printable materials with a high refractive index (HRI). Although solutions for thin layers (up to 100 nm) of HRI-materials are known, these thick layers remain an unsolved challenge from a cost or performance perspective.
[0070] It was therefore an object of the present invention to provide compositions which are suitable for producing coatings having a high refractive index, excellent chemical and mechanical stability and excellent light resistance.
[0071] An additional object of the present invention is to provide modified titanium dioxide nanoparticles and compositions comprising them which allow good curability (crosslinking of monomers) in thick layers at relatively low UV doses and which lead to coatings with excellent chemical and mechanical stability and excellent light resistance.
[0072] An additional object of the present invention is to provide a composition suitable for producing crosslinkable coatings having a high refractive index and a relatively high thickness.
[0073] An additional object of the present invention is to provide compositions suitable for producing relatively thin coatings having a high refractive index and good chemical, mechanical and light resistances.
[0074] "Cross-linked coating" means a three-dimensional network of polymer molecules formed by the monomers upon curing and the metal oxide particles embedded therein. Summary of the invention
[0075] Therefore, the present invention relates to a coating composition comprising
[0076] i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm,
[0077] ii) one or more monomers having at least three thiol groups (—SH) at the terminal ends (first monomers),
[0078] iii) optionally one or more monomers having at least two functional groups at the terminal ends capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer),
[0079] iv) one or more solvents. The coating composition is in particular a UV-Vis curable coating composition.
[0080] Compared to the particles described in the prior art, the coating compositions of the invention allow transparent, crosslinked, chemically and mechanically resistant coatings to be obtained having a high refractive index and thickness as well as light resistance.
[0081] The coating compositions of the present invention can be used to coat diffractive optical elements (DOEs), holograms, to make optical waveguides and solar panels, light outcoupling layers for display and lighting devices, high dielectric constant (high-k) gate oxides and interlayer high-k dielectrics, anti-reflective coatings, etch and CMP stop layers, optical thin film color filters, optical diffraction gratings and hybrid thin film diffraction grating structures, high refractive index wear resistant coatings - in protection and sealing (OLED), or organic solar cells.
[0082] The term "security document" refers to a document that is typically protected from counterfeiting or fraud by at least one security feature. Examples of security documents include, but are not limited to, documents of value and commercial items of value.
[0083] The terms "UV-Vis curable" and "UV-Vis curing" refer to radiation curing under the influence of radiation having a wavelength component in the UV or UV and visible part of the electromagnetic spectrum (typically 100 nm to 800 nm, preferably between 150 and 600 nm and more preferably between 200 and 400 nm). The irradiated coating has a higher mechanical and / or chemical stability than the non-irradiated coating. DETAILED DESCRIPTION
[0084] The coating composition of the present invention comprises, based on the total weight of one or more components i), ii), iii) and iv)
[0085] i) preferably 3 to 50% by weight of single or mixed metal oxide nanoparticles,
[0086] ii) preferably 0.15 to 10% by weight of one or more monomers having a triazine ring and at least three thiol groups (—SH) at the terminal ends (first monomer),
[0087] iii) preferably 0 to 30% by weight of one or more monomers having at least two functional groups at the terminal ends capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer), and
[0088] iv) preferably 20 to 96.9% by weight of one or more solvents.
[0089] In a preferred embodiment, the coating composition of the present invention does not contain the second monomer iii); that is, it is essentially composed of
[0090] i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm; and
[0091] ii) one or more monomers having at least three thiol groups (—SH) at the terminal ends (first monomers), and
[0092] iv) one or more solvents. The coating composition is in particular a UV-Vis curable coating composition.
[0093] The coating composition is particularly suitable for providing a ("thin") coating having a thickness of 0.01 to 0.50 micrometer, preferably 0.02 to 0.40 micrometer, more preferably 0.03 to 0.30 micrometer, most preferably 0.04 to 0.25 micrometer after drying and UV curing.
[0094] In the embodiments described, the coating composition of the present invention comprises, based on the total weight of one or more components i), ii), iii) and iv)
[0095] i) preferably 3.0 to 20.0% by weight, more preferably 4.0 to 10.0% by weight, of single or mixed metal oxide nanoparticles,
[0096] ii) preferably 0.1 to 3.0% by weight, more preferably 0.15 to 2.0% by weight, of one or more monomers having a triazine ring and at least three thiol groups (—SH) at the terminal ends (first monomer), and
[0097] iv) preferably from 77.0 to 96.9%, more preferably from 88.0 to 95.85% by weight of one or more solvents.
[0098] In another preferred embodiment, the coating composition of the present invention comprises
[0099] i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm; and
[0100] ii) one or more monomers having at least three thiol groups (—SH) at the terminal ends (first monomers),
[0101] iii) one or more monomers (second monomers) having at least two functional groups at the terminals capable of reacting with a thiol group and a spacer group between the at least two functional groups,
[0102] iv) one or more solvents. The coating composition is in particular a UV-Vis curable coating composition.
[0103] The coating composition is particularly suitable for providing a ("thick") coating having a thickness of 0.10 to 30.0 microns, preferably 0.20 to 20.0 microns, more preferably 0.30 to 10 microns, most preferably 0.50 to 6.0 microns after drying and UV curing.
[0104] In the embodiments described, the coating composition of the present invention comprises, based on the total weight of one or more components i), ii), iii) and iv)
[0105] i) preferably 5.0 to 50.0% by weight, more preferably 5.0 to 45.0% by weight, of single or mixed metal oxide nanoparticles,
[0106] ii) preferably 0.25 to 10.0% by weight, more preferably 0.30 to 8.0% by weight, of one or more monomers having a triazine ring and at least three thiol groups (—SH) at the terminal ends (first monomer),
[0107] iii) preferably 0.25 to 30.0% by weight, more preferably 0.3 to 22.0% by weight, of one or more monomers having at least two functional groups at the terminals capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer), and
[0108] iv) preferably 20.0 to 94.5%, more preferably 25 to 94.4% by weight of one or more solvents.
[0109] Furthermore, the coating composition of the present invention may contain an adhesion promoter, a surfactant, a leveling agent and a polymer binder.
[0110] Single or mixed metal oxide nanoparticles (component i)
[0111] The single or mixed metal oxide nanoparticles are preferably titanium dioxide nanoparticles, with a volume average diameter (D v 50) is in the range of 1 to 10 nm, preferably 1 to 5 nm.
[0112] In a particularly preferred embodiment, the single or mixed metal oxide nanoparticles are titanium dioxide nanoparticles, which contain at least one volatile surface modification compound selected from ethanol and acetylacetone and mixtures thereof, wherein the total amount of volatile surface modification compounds is in the range of 10 to 50% by weight, especially 10 to 40% by weight, very especially 15 to 35% by weight, based on the amount of metal oxide nanoparticles. Reference is made to WO 2022 / 038161.
[0113] A process for preparing a composition of single or mixed metal oxide nanoparticles may include the following steps:
[0114] a) preparing a mixture comprising one or more metal oxide precursor compounds, an ether-alcohol solvent, water and HCl,
[0115] b1) heating the reaction mixture to a temperature of 70° C. to 120° C.;
[0116] b2) separating the obtained metal oxide nanoparticles from the mixture;
[0117] b3) resuspending the metal oxide nanoparticles in alcohol, or a mixture of alcohols, or a mixture of alcohols and ketones;
[0118] b4) optionally treating the metal oxide nanoparticles with a volatile surface-modifying compound or a salt thereof selected from β-diketones and β-ketoesters and mixtures thereof; the volatile surface-modifying compound or a salt thereof is preferably selected from the formula Me(OR 20 ) x (L) y (V) or a mixture thereof, wherein
[0119] R 20 is C1-C8 alkyl, preferably C1-C4 alkyl, such as, for example, methyl, ethyl, n-propyl, isopropyl and n-butyl;
[0120] L - yes The group,
[0121] R 21 and R 22are independently C1-C8 alkyl; phenyl, which may be optionally substituted by one or more C1-C4 alkyl or C1-C4 alkoxy; C2-C5 heteroaryl, which may be optionally substituted by one or more C1-C4 alkyl or C1-C4 alkoxy; or C1-C8 alkoxy,
[0122] R 23 is a hydrogen atom, a fluorine atom, a chlorine atom, or a C1-C8 alkyl group, or
[0123] R 21 and R 22 together form a cyclic or bicyclic ring, which may be optionally substituted with one or more C1-C4 alkyl groups;
[0124] Me is selected from the group consisting of alkali metals and alkaline earth metals, Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V), Ta(V), preferably Zn(II), Ti(IV), Zr(IV), Hf(IV), Sn(IV), Nb(V) and Ta(V), more preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V),
[0125] x is in the range of 0 to 4.9, preferably 0 to 4.5, y is in the range of 0.1 to 5, preferably 0.5 to 5, and the sum of x+y is equal to the oxidation state of the metal Me;
[0126] c1) treating the metal oxide nanoparticles with a base, in particular a base selected from the group consisting of alkali metal alkoxides, alkali metal hydroxides and combinations thereof, more preferably alkali metal alkoxides and combinations thereof, most preferably potassium alkoxides and combinations thereof;
[0127] c2) optionally treating the metal oxide nanoparticles with a volatile surface modification compound or a salt thereof; and
[0128] c3) optionally with the formula Me'(OR 20 ') z (VII) or a mixture thereof to treat TiO2 nanoparticles; and
[0129] c4) filtering the mixture to obtain a dispersion of single or mixed metal oxide nanoparticles;
[0130] in
[0131] R 20 ' is a C1-C8 alkyl group, preferably a C1-C4 alkyl group;
[0132] Me' is selected from Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V) and Ta(V), preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V); and
[0133] z is equal to the oxidation state of the metal; where
[0134] The one or more metal oxide precursor compounds are selected from the group consisting of: 12 ) k (I) Metal alkoxide, metal halide Me'(Hal) l Japanese-style "Me" (Hal') m (OR 12 ') n (II) metal alkoxy halides and mixtures thereof, wherein
[0135] Me, Me' and Me" are independently titanium, tin, tantalum, niobium, hafnium or zirconium, especially titanium;
[0136] k represents the valence of the metal and is 4 or 5,
[0137] l represents the valence of the metal and is 4 or 5,
[0138] R 12 and R 12’ are independently C1-C8 alkyl;
[0139] Hal and Hal' are independently Cl, Br or I, preferably Cl;
[0140] m is an integer from 1 to 4;
[0141] n is an integer from 1 to 4;
[0142] m+n represents the valence of the metal Me” and is 4 or 5;
[0143] The solvent comprises at least one ether group and one alcohol group;
[0144] The ratio of the number of moles of water to the total number of moles of Me and Me' is in the range of 2:1 to 6:1, more preferably 2.8:1 to 5:1, especially 3:1 to 4.5:1;
[0145] The ratio of the total moles of Hal, Hal' and HCl to the total moles of Me, Me' and Me" is in the range of 2:1 to 0.3:1, preferably 1:1 to 0.35:1, especially 0.7:1 to 0.4:1.
[0146] The total amount of volatile surface-modifying compounds is at least 5% by weight, preferably at least 10% by weight, based on the amount of metal oxide nanoparticles.
[0147] The solvent used in step a) is preferably selected from the group consisting of 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, 1-butoxy-2-propanol and mixtures thereof.
[0148] More preferably, the solvent is selected from the group consisting of 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol and mixtures thereof.
[0149] The most preferred solvent is 1-methoxy-2-propanol.
[0150] Preferably, the mixture used in step a) comprises a metal alkoxide of formula (I).
[0151] The metal alkoxide of formula (I) is preferably of the formula Me(OR 12 )4(Ia) metal alkoxide, wherein R 12 It is a C1-C4 alkyl group.
[0152] Me'(Hal) x’ The metal halide of (II) is preferably a metal halide of the formula Me'(Hal)4(IIa), wherein Hal is Cl. Me' is preferably titanium.
[0153] The temperature in step b1) is preferably in the range of 80 to 120°C.
[0154] The one or more alcohols R formed in step b1) 12 OH and / or R 12’ OH can be removed from the reaction mixture by distillation. 12 OH and / or R 12’ The removal of OH can increase the reaction rate and / or product quality.
[0155] Separation of the metal oxide nanoparticles obtained from the mixture in step b2) can be done, for example, by filtration or centrifugation, preferably by filtration.
[0156] In step b3), the metal oxide nanoparticles are preferably resuspended in a C1-C4 alcohol, such as, for example, ethanol, 1-propanol and isopropanol; or a mixture of C1-C4 alcohols.
[0157] The base used in step c1) is preferably selected from the group consisting of alkali metal alkoxides and alkali metal hydroxides and combinations thereof. More preferably, the base is selected from the group consisting of alkali metal alkoxides, especially potassium alkoxides. The most preferred bases are potassium methoxide and potassium ethoxide.
[0158] The metal oxide nanoparticles can be treated with one or more volatile surface-modifying compounds selected from β-diketones and β-ketoesters and mixtures thereof (especially one or more β-diketones, such as, for example, acetylacetone) in step b4) and / or c2). The treatment with one or more volatile surface-modifying compounds is preferably completed in step b4).
[0159] After treatment with a base aliquot of the nanoparticle dispersion in ethanol mixed with water (1:2 v / v) under vigorous stirring, a pH greater than 3.5 was shown. This means that the obtained nanoparticles have low corrosiveness.
[0160] In a particularly preferred embodiment, the process for preparing a dispersion of single or mixed metal oxide nanoparticles (coating composition) involves preparing a dispersion of TiO2 nanoparticles and comprises the following steps:
[0161] a) preparing a mixture comprising a compound of formula Ti(OR 12 )4(Xa) metal alkoxide, solvent, HCl and water, wherein R 12 is C1-C4 alkyl, preferably methyl, ethyl, n-propyl, isopropyl and n-butyl;
[0162] b1) heating the mixture to a temperature of 80° C. to 100° C.;
[0163] b2) separating the obtained TiO2 nanoparticles from the mixture;
[0164] b3) resuspending the TiO2 nanoparticles in a C1-C4 alcohol or a mixture of C1-C4 alcohols;
[0165] b4) optionally treating the TiO2 nanoparticles with one or more β-diketones or one or more salts thereof;
[0166] c1) treating TiO2 nanoparticles with a base;
[0167] c2) optionally treating the TiO2 nanoparticles with one or more β-diketones or one or more salts thereof;
[0168] c3) optionally with the formula Me'(OR 20 ') z (VII) or a mixture thereof to treat TiO2 nanoparticles; and
[0169] c4) filtering the mixture to obtain a dispersion of TiO2 nanoparticles, wherein
[0170] R 20 ' is a C1-C8 alkyl group, preferably a C1-C4 alkyl group;
[0171] Me' is selected from Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V) and Ta(V), preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V); and
[0172] z is equal to the oxidation state of the metal; where
[0173] The solvent comprises at least one ether group and one alcohol group;
[0174] The ratio of the number of moles of water to the total number of moles of Me and Me' is in the range of 3:1 to 5:1, more preferably 3.2:1 to 4.5:1, especially 3.5:1 to 4.5:1;
[0175] The ratio of moles of HCl to moles of titanium is in the range of 1:1 to 0.3:1, preferably 0.8:1 to 0.35:1, especially 0.7:1 to 0.4:1.
[0176] The total amount of volatile surface-modifying compounds is at least 5% by weight, preferably at least 10% by weight, based on the amount of metal oxide nanoparticles.
[0177] The solvent used in step a) is preferably selected from the group consisting of 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, 1-butoxy-2-propanol and mixtures thereof.
[0178] More preferably, the solvent is selected from the group consisting of 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol and mixtures thereof.
[0179] The most preferred solvent is 1-methoxy-2-propanol.
[0180] The base is selected from potassium alkoxide or a combination thereof, preferably potassium methoxide and potassium ethoxide.
[0181] In the described embodiment, the process preferably comprises the following steps:
[0182] a) preparing a mixture comprising a compound of formula Ti(OR12 )4(Xa) metal alkoxide, solvent, HCl and water, wherein R 12 is C1-C4 alkyl, preferably methyl, ethyl, n-propyl, isopropyl and n-butyl;
[0183] b1) heating the mixture to a temperature of 80° C. to 100° C.;
[0184] b2) separating the obtained TiO2 nanoparticles from the mixture;
[0185] b3) resuspending the TiO2 nanoparticles in a C1-C4 alcohol or a mixture of C1-C4 alcohols;
[0186] b4) treating the TiO2 nanoparticles with one or more β-diketones or one or more salts thereof;
[0187] c1) treating TiO2 nanoparticles with a base;
[0188] c4) filtering the mixture to obtain a dispersion of TiO2 nanoparticles, wherein
[0189] The solvent was 1-methoxy-2-propanol;
[0190] The ratio of the number of moles of water to the total number of moles of Me and Me' is in the range of 3:1 to 5:1, more preferably 3.2:1 to 4.5:1, especially 3.5:1 to 4.5:1;
[0191] The ratio of moles of HCl to moles of titanium is in the range of 1:1 to 0.3:1, preferably 0.8:1 to 0.35:1, especially 0.7:1 to 0.4:1.
[0192] The separation of the TiO2 nanoparticles obtained from the mixture in step b2) can be done, for example, by filtration or centrifugation.
[0193] In step b3), the metal oxide nanoparticles are preferably resuspended in ethanol, 1-propanol and isopropanol; more preferably resuspended in ethanol.
[0194] In step b4) and / or c2) one or more β-diketones, for example, + L - Compounds (wherein L - The treatment with one or more β-diketones is preferably carried out in step b4). The treatment is generally carried out at a temperature of 0° C. to 120° C., preferably at a temperature of 20° C. to 100° C. The treatment is preferably carried out at atmospheric pressure or higher pressure, in particular at atmospheric pressure.
[0195] The base used in step c1) is preferably an alkali metal alkoxide, especially potassium alkoxide. The treatment is generally carried out at a temperature of 0° C. to 120° C., preferably 50° C. to 100° C. The treatment can be carried out at normal pressure or higher pressure, and is preferably carried out at normal pressure.
[0196] In step b4) and / or c2), the β-diketonate anion (L - ) are treated with one or more metal complexes of the formula Me(OR 20 ) x (L - ) y (V) or a mixture thereof, wherein:
[0197] R 20 is C1-C8 alkyl, preferably C1-C4 alkyl, such as, for example, methyl, ethyl, n-propyl, isopropyl and n-butyl;
[0198] L - yes The group,
[0199] R 21 and R 22 are independently C1-C8 alkyl; phenyl, which may be optionally substituted by one or more C1-C4 alkyl or C1-C4 alkoxy; C2-C5 heteroaryl, which may be optionally substituted by one or more C1-C4 alkyl or C1-C4 alkoxy; or C1-C8 alkoxy,
[0200] R 23 is a hydrogen atom, a fluorine atom, a chlorine atom, or a C1-C8 alkyl group, or
[0201] R 21 and R 22 together form a cyclic or bicyclic ring, which may be optionally substituted with one or more C1-C4 alkyl groups;
[0202] Me is selected from alkali metals and alkaline earth metals, Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V), Ta(V), preferably Zn(II), Ti(IV), Zr(IV), Hf(IV), Sn(IV), Nb(V) and Ta(V), more preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V);
[0203] x is in the range of 0 to 4.9, preferably 0 to 4.5, y is in the range of 0.1 to 5, preferably 0.5 to 5, and the sum of x+y is equal to the oxidation state of the metal.
[0204] The treatment is preferably carried out at a temperature of 0° C. to 120° C., in particular 20° C. to 100° C. The treatment is preferably carried out at normal pressure or higher pressure, in particular at normal pressure.
[0205] The process may further comprise an optional step c3) wherein Me'(OR 20 ') z (VII) or a mixture thereof, wherein the dispersion obtained in step c1) or step c2) is treated with a compound of
[0206] R 20 ' is a C1-C8 alkyl group, preferably a C1-C4 alkyl group;
[0207] Me' is selected from Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V) and Ta(V), preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V); and
[0208] z is equal to the oxidation state of the metal.
[0209] Preferred β-diketonate anions are obtained by removing a proton from acetylacetone, 2,4-hexanedione, 2,4-heptanedione, 3,5-heptanedione, 1,3-cyclohexanedione, 1,3-cyclopentanedione, especially acetylacetone.
[0210] Preferably, the metal oxide nanoparticles are treated with one or more β-diketones, such as, for example, acetylacetone, in step b4) and / or c2). The treatment with one or more β-diketones is preferably done in step b4).
[0211] After treatment with a base aliquot of the nanoparticle dispersion in ethanol mixed with water (1:2 v / v) under vigorous stirring, a pH greater than 3.5 was shown. This means that the obtained nanoparticles have low corrosiveness.
[0212] The metal oxide nanoparticles, especially titanium dioxide nanoparticles, used in the coating composition according to the present invention are preferably obtained by the above process.
[0213] The metal oxide nanoparticles, especially titanium dioxide nanoparticles, used in the coating composition according to the present invention are preferably obtained by the above process.
[0214] The volume average particle size of the metal oxide, especially titanium dioxide nanoparticles is 1 nm to 20 nm, preferably 1 nm to 10 nm, more preferably 1 nm to 5 nm. They can be resuspended in, for example, methanol, ethanol, propanol, 2-methoxyethanol, isopropanol, 2-isopropoxyethanol, 1-butanol, 1-methoxy-2-propanol and mixtures thereof with ketones such as 2-butanone, cyclopentanone, cyclohexanone. The film of the metal oxide, especially titanium dioxide nanoparticles dried and cured with UV light shows a refractive index of greater than 1.70 (at 589 nm), in particular greater than 1.80, very particularly greater than 1.90.
[0215] In a particularly preferred embodiment, the coating composition (dispersion) according to the present invention comprises i) titanium dioxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 10 nm, in particular 1 to 5 nm; the nanoparticles contain at least one volatile surface-modifying compound selected from ethanol and acetylacetone and mixtures thereof, wherein the total amount of volatile surface-modifying compounds is in the range of 10 to 50% by weight, in particular 10 to 40% by weight, very particularly 15 to 35% by weight, based on the amount of metal oxide nanoparticles;
[0216] ii) a first monomer having the formula Compound (trithiocyanuric acid);
[0217] iii) a second monomer selected from the group consisting of bis(4-vinylthienyl) sulfide, bis(4-methacryloylthienyl) sulfide, dipropylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate, octanediol diacrylate, Acrylates, octanediol dimethacrylate, nonanediol diacrylate, nonanediol dimethacrylate, decanediol diacrylate, decanediol dimethacrylate, cyclohexanediol diacrylate, cyclohexanediol dimethacrylate, cyclohexanedimethanol diacrylate, cyclohexanedimethanol dimethacrylate, (ethoxylated) neopentyl glycol diacrylate, (propoxylated) neopentyl glycol diacrylate, (ethoxylated) neopentyl glycol dimethacrylate, (propoxylated) neopentyl glycol dimethacrylate, trihydroxymethyl trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane trimethacrylate, ethoxylated glycerol triacrylate, ethoxylated glycerol trimethacrylate, propoxylated glycerol triacrylate, propoxylated glycerol trimethacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane ethoxylated ditrimethylolpropane tetraacrylate, propoxylated ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, propoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetramethacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, propoxylated dipentaerythritol hexaacrylate, and mixtures thereof; and
[0218] iv) a solvent selected from the group consisting of C2-C4 alcohols, especially ethanol, 1-propanol and isopropanol; ketones, especially acetone, 2-butanone, 2-pentanone, 3-pentanone, cyclopentanone and cyclohexanone; ether alcohols, especially 1-methoxy-2-propanol; and mixtures thereof.
[0219] First monomer (component ii)
[0220] The first monomer preferably has a triazine structure and three thiol groups (—SH) at the terminals.
[0221] The most preferred first monomer is of formula of the compound (trithiocyanuric acid).
[0222] Second monomer (component iii))
[0223] The second monomer having at least two functional groups at the terminal ends that are capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer) may be a difunctional, trifunctional, tetrafunctional, pentafunctional, or hexafunctional diluent having two, three, four, five, or six unsaturated carbon-carbon bonds, in particular a difunctional (meth)acrylate, a trifunctional (meth)acrylate, a tetrafunctional (meth)acrylate, a pentafunctional (meth)acrylate, or a hexafunctional (meth)acrylate.
[0224] Examples of difunctional (meth)acrylates are bisphenol A ethoxylated diacrylate, bisphenol A glycerol diacrylate, glycerol diacrylate, triglycerol diacrylate, poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) diacrylate, tricyclo[5.2.1.0 2,6 ] decanedimethanol diacrylate, (ethoxylated) trimethylolpropane methyl ether diacrylate, (propoxylated) trimethylolpropane methyl ether diacrylate, cyclohexanediol diacrylate, cyclohexanedimethanol diacrylate, cyclohexanedimethanol diacrylate, bisphenol A ethoxylated dimethacrylate, bisphenol A glycerol dimethacrylate, glycerol dimethacrylate, triglycerol dimethacrylate, poly (ethylene glycol) -block - poly (propylene glycol) -block - poly (ethylene glycol) dimethacrylate, tricyclo[5.2.1.0 2,6 ] decanedimethanol dimethacrylate, (ethoxylated) trimethylolpropane methyl ether dimethacrylate, (propoxylated) trimethylolpropane methyl ether dimethacrylate, cyclohexanediol dimethacrylate and cyclohexanedimethanol dimethacrylate.
[0225] The difunctional (meth)acrylate is preferably a compound of the formula
[0226]
[0227] R 11 is independently at each occurrence H, or methyl;
[0228] X 1 Is a group of the formula
[0229]
[0230] in
[0231] m1 is 0 or 1; m2 is 0 or 1;
[0232] m3 is 0, or an integer from 1 to 10; m4 is 0, or an integer from 1 to 10;
[0233] m5 is an integer from 0, 1 to 8;
[0234] z' is 0 or 1;
[0235] R 42 is independently H, or C1-C4 alkyl at each occurrence;
[0236] R 40 , R 41 , R 43 , R 44 , R 45 and R 46 are independently H, or C1-C4 alkyl.
[0237] Examples of difunctional (meth)acrylates of formula (XXa) are propylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tetrapropylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, 1,3-propylene glycol diacrylate, 1,2-butanediol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, pentanediol diacrylate, hexanediol diacrylate, (ethoxylated) 1,4-butanediol diacrylate, (propoxylated) 1,4-Butanediol diacrylate, (ethoxylated) 1,5-pentanediol diacrylate, (propoxylated) 1,5-pentanediol diacrylate, (ethoxylated) 1,6-hexanediol diacrylate, (propoxylated) 1,6-hexanediol diacrylate, (ethoxylated) 1,8-octanediol diacrylate, (propoxylated) 1,8-octanediol diacrylate, (ethoxylated) neopentyl glycol diacrylate, (propoxylated) neopentyl glycol diacrylate, propylene glycol dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, tetrapropylene glycol dimethacrylate Glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-propylene glycol dimethacrylate, 1,2-butylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, pentanediol dimethacrylate, hexanediol dimethacrylate, (ethoxylated) 1,4-butylene glycol dimethacrylate, (propoxylated) 1,4-butylene glycol dimethacrylate, (ethoxylated) 1,5-pentanediol dimethacrylate Methacrylate, (propoxylated) 1,5-pentanediol dimethacrylate, (ethoxylated) 1,6-hexanediol dimethacrylate, (propoxylated) 1,6-hexanediol dimethacrylate, (ethoxylated) 1,8-octanediol dimethacrylate, (propoxylated) 1,8-octanediol dimethacrylate, (ethoxylated) neopentyl glycol dimethacrylate, (propoxylated) neopentyl glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, poly(propylene glycol) diacrylate, poly(propylene glycol) dimethacrylate.
[0238] Examples of trifunctional (meth)acrylates are trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ethoxylated trimethylolpropane triacrylates (in particular selected from the group consisting of ethoxylated (EO3) trimethylolpropane triacrylate, ethoxylated (EO6) trimethylolpropane triacrylate, ethoxylated (EO9) trimethylolpropane triacrylate), propoxylated trimethylolpropane triacrylate (PO3 TMPTA), ethoxylated glycerol triacrylate and propoxylated glycerol triacrylate (GPTA), pentaerythritol triacrylate (PETA), a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate, ethoxylated pentaerythritol triacrylate, propoxylated pentaerythritol triacrylate (ethoxylated (EO3) pentaerythritol triacrylate, ethoxylated (EO6) pentaerythritol triacrylate, ethoxylated (EO9) pentaerythritol triacrylate) and mixtures thereof.
[0239] Examples of tetrafunctional (meth)acrylates are ditrimethylolpropane tetraacrylate (DiTMPTA), pentaerythritol tetraacrylate (PETA), pentaerythritol tetramethacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, ethoxylated ditrimethylolpropane tetraacrylate, propoxylated ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate (EPETA), propoxylated pentaerythritol tetraacrylate, dipentaerythritol tetraacrylate, ethoxylated dipentaerythritol tetraacrylate, propoxylated dipentaerythritol tetraacrylate, and mixtures thereof.
[0240] Examples of pentafunctional (meth)acrylates are dipentaerythritol pentaacrylate, sorbitol pentaacrylate and mixtures thereof.
[0241] Examples of hexafunctional (meth)acrylates are dipentaerythritol hexaacrylate, 1290 (which is a hexafunctional aliphatic urethane hexaacrylate) and mixtures thereof.
[0242] More preferably, the reactive diluent having at least two ethylenically unsaturated groups in the molecule is selected from bis(4-vinylthienyl) sulfide, bis(4-methacryloylthienyl) sulfide, dipropylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, hexanediol diacrylate, Hexanediol dimethacrylate, octanediol diacrylate, octanediol dimethacrylate, nonanediol diacrylate, nonanediol dimethacrylate, decanediol diacrylate, decanediol dimethacrylate, cyclohexanediol diacrylate, cyclohexanediol dimethacrylate, cyclohexanedimethanol diacrylate, cyclohexanedimethanol dimethacrylate, (ethoxylated) neopentyl glycol diacrylate, (propoxylated) neopentyl glycol diacrylate, (ethoxylated) neopentyl glycol dimethacrylate, (propoxylated) neopentyl glycol dimethacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane trimethacrylate, ethoxylated glycerol triacrylate, ethoxylated glycerol trimethacrylate, propoxylated glycerol triacrylate, propoxylated glycerol trimethacrylate, ditrimethylolpropane tetraacrylate esters, ditrimethylolpropane tetramethacrylate, ethoxylated ditrimethylolpropane tetraacrylate, propoxylated ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, propoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetramethacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, propoxylated dipentaerythritol hexaacrylate, and mixtures thereof.
[0243] In addition to the reactive diluent having at least 2 ethylenically unsaturated groups in the molecule, the composition of the present application may also contain a monofunctional diluent.
[0244] Examples of monofunctional vinylamides include N-vinyl-pyrrolidone, N-vinylcaprolactam, N-(hydroxymethyl)vinylamide, N-hydroxyethylvinylamide, N-isopropylvinylamide, N-isopropylmethylvinylamide, N-tert-butylvinylamide, N,N'-methylenebisvinylamide, N-(isobutoxymethyl)vinylamide, N-(butoxymethyl)vinylamide, N-[3-(dimethylamino)propyl]methylvinylamide, N,N-dimethylvinylamide, N,N-diethylvinylamide and N-methyl-N-vinylacetamide.
[0245] Examples of the monofunctional (meth)acrylamide include acryloylmorpholine, methacryloylmorpholine, N-(hydroxymethyl)acrylamide, N-hydroxyethylacrylamide, N-isopropylacrylamide, N-isopropylmethacrylamide, N-tert-butylacrylamide, N,N'-methylenebisacrylamide, N-(isobutoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, N-[3-(dimethylamino)propyl]methacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-(hydroxymethyl)methacrylamide, N-hydroxyethylmethacrylamide, N-isopropylmethacrylamide, N-isopropylmethylmethacrylamide, N-tert-butylmethacrylamide, N-(isobutoxymethyl)methacrylamide, N-(butoxymethyl)methacrylamide, N-[3-(dimethylamino)propyl]methylmethacrylamide, N,N-dimethylmethacrylamide, and N,N-diethylmethacrylamide.
[0246] Another example of a monofunctional diluent is
[0247] Mode N-vinyl oxazolidinone, wherein
[0248] R 61 , R 62 , R 63 and R 64 are independently a hydrogen atom or an organic group having not more than 10 carbon atoms, such as, for example, N-vinyloxazolidinone (NVO) or N-vinyl-5-methyloxazolidinone (NVMO);
[0249] N-vinyl-pyrrolidone (NVP), N-vinyl-caprolactam (NVC), trimethylolpropane formal (meth)acrylate, such as (Trimethylolpropane formal acrylate) (trimethylolpropane formal methacrylate);
[0250] -Di(meth)acrylamide of the following formula
[0251] in
[0252] R 11 is independently at each occurrence H, or methyl,
[0253] X 1 Is a group of the formula
[0254]
[0255] in
[0256] m1 is 0 or 1; m2 is 0 or 1;
[0257] m3 is 0, or an integer from 1 to 10; m4 is 0, or an integer from 1 to 10;
[0258] m5 is 0, or an integer from 1 to 8;
[0259] R 42 is independently H, or C1-C4 alkyl at each occurrence;
[0260] R 40 , R 41 , R 43 , R 44 , R 45 and R 46 are independently H, or C1-C4 alkyl.
[0261] Examples of monofunctional (meth)acrylates include, but are not limited to, octyl acrylate; decyl acrylate; lauryl acrylate, tridecyl acrylate; isodecyl acrylate; stearyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, octyl methacrylate, lauryl methacrylate, isodecyl methacrylate, tridecyl methacrylate; tetradecyl methacrylate; isodecyl methacrylate and stearyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate; isobornyl acrylate; 4-tert-butylcyclohexyl acrylate; cyclohexyl methacrylate, isobornyl methacrylate, tetrahydrofurfuryl acrylate, (5-ethyl-1,3-dioxane-5-yl)methyl acrylate, ethoxylated phenyl acrylate, ethoxylated phenyl methacrylate, nonylphenol acrylate, nonylphenol methacrylate, methoxypolyethylene glycol acrylate, methoxy methacrylate, methoxypolypropylene glycol acrylate, methoxypolypropylene glycol methacrylate, tetrahydrofurfuryl methacrylate, cyclic trimethylolpropane formal methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and glycidyl acrylate, N-(2-hydroxyethyl) acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and glycidyl methacrylate, benzyl acrylate, 2-phenoxyethyl acrylate, ethoxylated (EO4) phenol acrylate; a mixture of ethoxylated (EO4) phenol acrylate and ethoxylated (EO8) nonylphenol acrylate; propoxylated (PO2) nonylphenol acrylate, ethoxylated o-phenylphenol acrylate, p-cumylphenoxyethyl acrylate, dicyclopentenyl acrylate and dicyclopentenyloxyethyl acrylate and 2-(N-butylcarbamoyloxy)ethyl acrylate.
[0262] The monofunctional (meth)acrylate may include hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate, N-(2-hydroxyethyl) acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, benzyl acrylate, and glycidyl methacrylate.
[0263] In a preferred embodiment of the invention, the second monomer (component iii) comprises a reactive diluent having a refractive index higher than 1.53, especially higher than 1.60, very especially higher than 1.70, such as, for example, (meth)acrylates, epoxides and episulfides. Acrylates, epoxides and episulfides, each having a functionality greater than 1, are self-crosslinking radiation-curing compound systems.
[0264] Preferred acrylates are, for example,
[0265] -2-((1,3-dithiolan-2-yl)methylthio)ethyl methacrylate Muchintala Maheswara et al., Polymer Journal 42 (2010) pp. 249-255),
[0266] -phenylthioethyl acrylate with a refractive index of 1.557 ( PTEA), and
[0267] -Bis(4-methacryloylthienyl)sulfide with a refractive index of 1.695 MPSMA).
[0268] In a preferred embodiment, the reactive diluent having at least two ethylenically unsaturated groups in the molecule is selected from bis(4-methacryloylthienyl)sulfide, dipropylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate. esters, octanediol diacrylate, octanediol dimethacrylate, nonanediol diacrylate, nonanediol dimethacrylate, decanediol diacrylate, decanediol dimethacrylate, cyclohexanediol diacrylate, cyclohexanediol dimethacrylate, cyclohexanedimethanol diacrylate, cyclohexanedimethanol dimethacrylate, (ethoxylated) neopentyl glycol diacrylate, (propoxylated) neopentyl glycol diacrylate, (ethoxylated) neopentyl glycol dimethacrylate, (propoxylated) neopentyl glycol dimethacrylate esters, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane trimethacrylate, ethoxylated glycerol triacrylate, ethoxylated glycerol trimethacrylate, propoxylated glycerol triacrylate, propoxylated glycerol trimethacrylate, ditrimethylolpropane tetraacrylate, Ditrimethylolpropane tetramethacrylate, ethoxylated ditrimethylolpropane tetraacrylate, propoxylated ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, propoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetramethacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, propoxylated dipentaerythritol hexaacrylate and mixtures thereof.
[0269] Solvent (component iv)
[0270] The solvent is preferably selected from C2-C4 alcohols, especially ethanol, 1-propanol and isopropanol; ketones, especially acetone, 2-butanone, 2-pentanone, 3-pentanone, cyclopentanone and cyclohexanone; ether alcohols, especially 1-methoxy-2-propanol; mixtures thereof and mixtures thereof with esters, especially ethyl acetate, 1-propyl acetate, isopropyl acetate and butyl acetate.
[0271] Most preferably, the solvent is selected from C2-C4 alcohols, especially ethanol, 1-propanol and isopropanol and mixtures thereof with ketones, especially 2-butanone, 2-pentanone, 3-pentanone, cyclopentanone and cyclohexanone, or ether alcohols, especially 1-methoxy-2-propanol.
[0272] The weight ratio of the second monomer iii) to the titanium dioxide nanoparticles i) is in the range of 4% to 100% w / w of the second monomer iii), preferably 5% to 75% w / w of the second monomer iii), more preferably 10% to 50% of the second monomer iii) relative to the titanium dioxide nanoparticles i).
[0273] In addition, the composition may include one or more oligomers. The oligomer is preferably selected from (meth) acrylic acid oligomers, urethane (meth) acrylate oligomers, polyester (meth) acrylate oligomers, polyether (meth) acrylate oligomers, amine-modified polyether (meth) acrylate oligomers, or epoxy (meth) acrylate oligomers, more preferably urethane (meth) acrylate oligomers, polyester (meth) acrylate oligomers, polyether (meth) acrylate oligomers, and epoxy (meth) acrylate oligomers and mixtures thereof.
[0274] The coatings obtainable from the coating compositions according to the invention have a refractive index (at 589 nm) of greater than 1.7, in particular greater than 1.8, very particularly greater than 1.9.
[0275] The coating obtained from the composition of the present application after exposure to UV light preferably has a transmission value of greater than 85%, more preferably greater than 90%, most preferably greater than 95% in the wavelength range from 400 to 750 nm.
[0276] Where the coating composition of the present invention comprises components i), ii), iii) and iv), the thickness of the cured coating after drying and UV curing is in the range of 0.1 to 30 microns, preferably 0.2 to 20 microns, more preferably 0.3 to 10 microns, most preferably 0.5 to 6 microns.
[0277] In case the coating composition of the present invention does not comprise component iii), after drying and UV curing, the thickness of the cured coating is in the range of 0.01 to 0.50 micrometer, preferably 0.02 to 0.40 micrometer, more preferably 0.03 to 0.30 micrometer, most preferably 0.04 to 0.25 micrometer.
[0278] A method for forming a coating having a high refractive index on a substrate comprises the following steps:
[0279] a) providing a substrate, preferably with a surface relief nano- and / or micro-structure;
[0280] b) applying the coating composition according to the invention to a substrate by wet coating or printing;
[0281] c) removing the solvent; and
[0282] d) exposing the dry coating to actinic radiation, especially UV light.
[0283] Furthermore, the invention relates to a security or decorative element comprising a substrate, which may comprise markings or other visible features in or on its surface; and a coating according to the invention or obtained by the method according to the invention on at least a portion of the surface of said substrate.
[0284] The expression "surface relief" is used to refer to non-planar portions of the surface of a substrate or layer, and typically defines a plurality of ridges and depressions. In a particularly advantageous embodiment, the surface relief structure is a diffractive surface relief structure. The diffractive surface relief structure may be a diffraction grating (such as a square grating, a sinusoidal grating, a sawtooth grating or a blazed grating), a hologram surface relief or another diffractive device that exhibits different appearances at different viewing angles, such as diffractive colors and holographic reproduction (e.g. like a lens, or a microprism). For the purposes of this specification, such surface relief structures will be referred to as diffractive optically variable image devices (DOVIDs).
[0285] In embodiments, the high refractive index (HRI) layer obtained from the coating composition of the present invention may further comprise a dispersion of scattering particles having a size along at least one axis such that the HRI layer exhibits a first color when viewed in reflection and a second, different color when viewed in transmission.
[0286] The coatings of the invention can be used to produce surface relief micro- and nanostructures, such as, for example, optically variable devices (OVDs), such as, for example, holograms.
[0287] A method for forming a surface relief micro- and / or nanostructure on a substrate, the method comprising the following steps:
[0288] a) forming surface relief micro- and / or nanostructures on discrete portions of a substrate;
[0289] b) depositing a coating composition according to the invention on at least a portion of the surface relief micro- and / or nanostructure;
[0290] c) removing the solvent; and
[0291] d) curing the dry coating by exposing it to actinic radiation, especially UV light.
[0292] Another specific embodiment of the present invention relates to a preferred method for forming a surface relief micro- and / or nanostructure on a substrate, wherein step a) comprises
[0293] a1) applying a curable compound to at least a portion of a substrate;
[0294] a2) contacting at least a portion of the curable compound with a surface relief micro- and / or nanostructure forming device; and
[0295] a3) Curing the curable compound.
[0296] Alternatively, the method for forming a surface relief micro- and / or nanostructure on a substrate comprises the following steps:
[0297] a') providing a substrate sheet, the sheet having an upper surface and a lower surface;
[0298] b') depositing a coating composition according to the invention on at least a portion of the upper surface;
[0299] c') removing the solvent;
[0300] d') forming a surface relief micro- and / or nanostructure on at least a portion of the coating composition, and
[0301] e') curing the dry coating obtained in step d') by exposing it to actinic radiation, in particular UV light.
[0302] Yet alternatively, the method for forming a surface relief micro- and / or nanostructure on a substrate comprises the following steps:
[0303] a'') providing a substrate sheet, the sheet having an upper surface and a lower surface;
[0304] b'') depositing a coating composition according to any one of claims 1 to 8 on at least a portion of the upper surface;
[0305] c'') removing the solvent;
[0306] d'') forming a surface relief micro- and / or nanostructure on at least a portion of the coating composition, so that the micro- or nanostructure is at least partially formed in the substrate;
[0307] e'') curing the dry coating obtained in step d") by exposing it to actinic radiation, in particular UV light.
[0308] The (coating) composition of the invention can be applied to the substrate by conventional printing presses such as gravure, flexographic, inkjet, lithographic, offset, letterpress and / or screen printing or other printing processes.
[0309] In another embodiment, the composition can be applied by coating techniques such as spraying, dipping, casting, or spin coating.
[0310] Preferably, the printing process is performed by gravure printing, flexographic printing, or by inkjet printing.
[0311] The resulting coating containing TiO2 nanoparticles is transparent in the visible light region.
[0312] The transparent layer containing TiO2 nanoparticles has a thickness in the range of 0.01 to 0.50 microns, preferably 0.02 to 0.40 microns, more preferably 0.03 to 0.30 microns, and most preferably 0.04 to 0.25 microns after drying and UV curing; or the transparent layer containing TiO2 nanoparticles has a thickness in the range of 0.10 to 30.0 microns, preferably 0.20 to 20.0 microns, more preferably 0.30 to 10 microns, and most preferably 0.50 to 6.0 microns after drying and UV curing.
[0313] The coating containing TiO2 nanoparticles is preferably dried below 120°C to avoid damage to the organic substrate and / or the coating.
[0314] The resulting product can be coated with a protective coating to increase durability and / or prevent duplication of the security element. The protective coating is preferably transparent or translucent. The protective coating can have a refractive index of about 1.2 to about 1.75. Examples of such coatings are known to the technician. For example, water-based coatings, UV-curable coatings or laminated coatings can be used. Examples of typical coating resins will be given below. Coatings with very low refractive indices are, for example, described in US 7821691, WO2008011919 and WO 2013117334.
[0315] The composition can be applied to an organic foil by gravure printing, followed by a clear topcoat and subsequently UV cured (e.g. Lumogen OVD Varnish ).
[0316] High refractive index coating according to the present invention can represent the dielectric layer in so-called Fabry Perot (Fabry Perot) element. With reference to for example (EP 1504923, WO 01 / 03945, WO 01 / 53113, WO 05 / 38136, WO16173696). In the described embodiment, safety element comprises the multilayer structure that can interfere, wherein the multilayer structure that can interfere has reflecting layer, dielectric layer and part transparent layer (EP 1504923, WO 01 / 03945, WO 01 / 53113, WO 05 / 38136, WO 16173696), wherein dielectric layer is arranged between reflecting layer and part transparent layer.
[0317] Suitable materials for the reflective layer include aluminum, silver, copper mixtures or their alloys. The partially transparent layer can be made of a semi-opaque material with a suitable thickness of about 3 to 15 nm, and the semi-opaque material includes metals such as chromium, nickel, titanium, vanadium, cobalt and palladium and other metals such as iron, tungsten, molybdenum, niobium and aluminum. Various combinations and alloys of the above metals can also be utilized, such as Inconel (Ni-Cr-Fe). Other partially transparent materials include metal compounds, such as metal fluorides, metal oxides, metal sulfides, metal nitrides, metal carbides, metal phosphides, metal selenides, metal silicides, and combinations thereof.
[0318] The reflective layer is preferably an aluminum or silver layer, and the dielectric layer is preferably formed from the (surface-functionalized) TiO2 nanoparticles according to the invention.
[0319] The high refractive index coating according to the invention may represent a partially transparent layer and / or a reflective layer of a Fabry-Perot resonator system. The reflective layer may also be partially transparent.
[0320] In a further embodiment, the high refractive index coating according to the invention may represent a semi-transparent layer of a Fabry-Perot resonator system, and the second semi-transparent layer may be represented by a continuous metal layer deposited, for example, by a thermal evaporation method or by a layer comprising discrete metal nanostructures capable of absorbing light in the visible wavelength range due to surface plasmon resonance, the layer comprising discrete metal nanostructures being deposited, for example, by vapor phase metallization on a surface relief nanostructure or by printing or coating a composition comprising metal nanoparticles (especially copper, silver or gold nanoparticles) ("plasmonic layer", see, for example, WO 2011 / 064162, WO 2012 / 176126, WO 2020 / 083794 and WO 2020 / 224982). The resulting optical effect observed from the side of the second semi-transparent layer is a colored metal reflection modified in reflection by the interference color of the dielectric system. The optical effect in reflection observed from the high refractive index coating is a pure interference color generated by the Fabry-Perot resonator system. In transmission, observed from either the first or second surface, the color is a subtractive mixture of the absorption color from the plasmon layer and the complementary color of the interference color of the Fabry-Perot resonator.
[0321] Plasma layers can also be produced by depositing a metal precursor composition on an underlying substrate or functional layer and exposing it to heat or actinic radiation, as described, for example, in WO 2016 / 170160 A1, WO 2018 / 210597 and WO 2019 / 020682 A1.
[0322] The high refractive index coating according to the invention can be used to produce thin film multilayer anti-reflective or reflective elements and coatings, which include stacks of layers with different refractive indices. See, for example, H.A. Macleod, "Thin-Film Optical Filters", published by Phys. Soc. Am. Verlag, 3rd ed., 2001; EP 2806293 A2 and DE 102010009999 A1.
[0323] In an additional embodiment, the present invention relates to a security or decorative element comprising a substrate, which may include markings or other visible features in or on its surface; and a coating according to the present invention or a coating obtained by a method according to the present invention on at least a portion of the surface of the substrate.
[0324] The security element may comprise one or more further functional layers selected from a black layer, a white layer, a continuous metal layer deposited, for example, by a thermal evaporation method, a layer comprising discrete metal nanostructures capable of absorbing light in the visible wavelength range due to surface plasmon resonance (which may be deposited, for example, by vapor metallization deposition on a surface relief nanostructure or by printing or coating a composition comprising metal nanoparticles), a layer comprising a surface relief nano- and / or microstructure such as DOE, micromirrors, microlenses, a layer comprising magnetic pigments, a cholesteric liquid crystal layer, a fluorescent layer, an interference layer such as, for example, a Fabry-Perot stack; a coloured layer, an IR absorbing layer, a coloured IR transparent layer, a conductive layer, an adhesive layer and a release layer.
[0325] The functional layer can be completely or partially printed on the substrate and / or the underlying layer.
[0326] The security element of the invention may be provided as a laminate on a security document, or as a window on a security document, or embedded in a security document as a (windowing) thread.
[0327] The security document of the present invention is selected from the group consisting of banknotes, stamps, ID cards, vouchers, entry tickets and labels.
[0328] If applied on top of the surface relief nano- and / or micro-structures, the high refractive index layer may conformally adhere to the surface relief nano- and / or micro-structures, or at least partially flatten the surface relief nano- and / or micro-structures. Reference is made to EP 2042343A1 and WO 2011116419. In this context, (partial) flattening means that the difference in distance between the highest feature of the relief structure and the lowest feature of the relief structure in the coated structure is reduced compared to the uncoated structure. In this context, complete flattening means that the difference in distance between the highest feature of the relief structure and the lowest feature of the relief structure is zero.
[0329] The HRI coating composition of the present invention can be applied by printing onto at least a portion of the surface relief nano- and / or micro-structure or onto the entire structure.
[0330] In a particularly preferred embodiment, the present invention relates to
[0331] - a security element comprising, in this order
[0332] i) overprint varnish layer, PET layer, adhesive layer, or release layer;
[0333] ii) a color conversion layer, such as, for example, a cholesteric liquid crystal layer;
[0334] iii) a layer of partial black printing or negative microtext;
[0335] iv) HRI coatings of the invention which flatten the surface relief nano- and / or micro-structures (v);
[0336] v) surface relief nano- and / or micro-structures;
[0337] vi) optionally a PET layer;
[0338] vii) optionally one or more functional layers comprising fluorescent materials, magnetic materials, NIR materials and conductive materials; and
[0339] viii) an overprint varnish layer, a PET layer, an adhesive layer, or a release layer; or
[0340] - a security element comprising, in this order
[0341] i) overprint varnish layer, PET layer, adhesive layer, or release layer;
[0342] ii) a color conversion layer, such as, for example, a cholesteric liquid crystal layer;
[0343] iii) a layer of partial black printing or negative microtext;
[0344] iiia) optionally planarizing the layer;
[0345] iv) an HRI coating of the invention conformally adhered to the surface relief nano- and / or micro-structure (v);
[0346] v) surface relief nano- and / or micro-structures;
[0347] vi) optionally a PET layer;
[0348] vii) optionally one or more functional layers comprising fluorescent materials, magnetic materials, NIR materials and conductive materials; and
[0349] viii) overprinting a varnish layer, a PET layer, an adhesive layer, or a release layer;
[0350] In another preferred embodiment, the invention relates to a safety device substantially as described in WO 2009 / 066048.
[0351] WO 2009 / 066048 relates to a security device (10) comprising a first and a second layer (11a, 11b) of a color change material at least partially overlapping each other and each having different color change properties; and a light control layer (12) applied at least partially on the exposed surface of one of the color change layers (11a, 11b) having a surface structure that changes the angle of reflected light so that light reflected by the security device is seen at different viewing angles and in at least one area; and a light absorbing layer (30) between the two color change layers (11a, 11b). The HRI coating of the present invention may be a light control layer 12 that will allow the light control layer 12 to be overvarnished and flattened with an overprint varnish. Alternatively, the light control layer 12 may be overcoated with the HRI composition of the present invention.
[0352] In Figure 16 of WO 2009 / 066048, a security device 10 comprises a first layer 11a of optically variable liquid crystal material and a second layer 11b of optically variable liquid crystal material, the second layer exhibiting different reflective properties than the first layer 11a. A partial absorbing layer 30 is applied between the first liquid crystal layer 11a and the second liquid crystal layer 11b. A light control layer 12 comprising a series of parallel linear microprisms is applied to the second liquid crystal layer 11b. The light control layer 12 may be a partial layer, as described with reference to Figure 4, or a full layer. If the device 10 is intended to be viewed in reflection, it is preferred to have an additional dark absorbing layer 31 present below the first liquid crystal layer 11a.
[0353] Applying a partially absorbing layer 30 between the two liquid crystal layers 11a, 11b creates two optically variable regions, namely regions A and B. In region A, there is no absorbing layer 30 between the two liquid crystal layers 11a, 11b, so that at any given angle of incidence, the wavelength of the reflected light is the result of an additive mixture of the individual wavelengths of light reflected from the two liquid crystal layers 11a, 11b. In region B, there is an absorbing layer 30 between the two liquid crystal layers, and at any given angle of incidence, the wavelength of the reflected light is only the reflected light from the second liquid crystal layer 11b.
[0354] The absorption layer 31 located below the first liquid crystal film layer 11a can be applied in a designed form to produce an additional optically variable region C, as shown in Figure 17 of WO 2009 / 066048. In region C, there is no absorption layer below any of the liquid crystal layers 11a, 11b, and when the device 10 is positioned on a reflective background, the intensity of the transmitted color reflected back by the liquid crystal layers 11a, 11b saturates the reflected color. The transmitted color and the reflected color are complementary, for example, a red to green color change in reflection is seen as a cyan to magenta color change in transmission.
[0355] In another preferred embodiment, the present invention relates to a security device 10 as generally described in Figure 1 of WO 2013 / 017865. Figure 1 of WO 2013 / 017865 shows a security device 10 comprising a carrier substrate 11. The substrate 11 is preferably a translucent or transparent polymer film, such as polyethylene (PET) or biaxially oriented polypropylene (BOPP). A light deflecting structure 12 is applied to the substrate 11, as a separate layer or formed in the surface of the substrate 11. The light deflecting structure 12 is a light deflecting structure having facets or lenses, which, when provided with a reflective coating 14, reflects light substantially strongly back to the light source when the light source is substantially parallel to the normal of the substrate and when the light source is away from the normal relative to the security device 10. One form of a suitable light reflecting structure 12 comprises a prismatic structure comprising a series of adjacent parallel linear prisms 17, wherein the planar facets are arranged to form a grooved surface. These can be formed by hot embossing prisms into the substrate 11 or by casting prisms into a resin that can be cured by ultraviolet light or electron beam irradiation. Other examples of suitable light deflecting structures 12 include, but are not limited to, regular arrays of tetrahedrons, arrays of square pyramids, arrays of rectangular structures, arrays of hexagonal faces, and arrays of sawtooth prisms. Other structures such as Fresnel lenses and biconvex lenses can also be used. The light deflecting structures 12 are then provided with positive or negative markings 13 by coating or covering selected areas 15 of the light deflecting structures 12 with the HRI coating 14 of the present invention, while leaving other areas 16 uncoated or uncovered.
[0356] The above-mentioned security device of the category can be incorporated into or applied to any article that wishes authenticity inspection. In particular, such devices can be applied to or incorporated into valuable documents, such as banknotes, passports, driver's licenses, checks, identity cards, etc. The security device or article can be completely arranged on the surface of the base substrate of the security document, such as in the case of stripes or patches, or can only be partially visible on the surface of the document substrate, such as in the form of a windowed security thread. At present, security threads are present in many currencies in the world as well as vouchers, passports, traveler's checks and other documents. In many cases, the thread is provided in a partially embedded or windowed manner, wherein the thread appears to be woven inside and outside the paper and visible in a window in one or two surfaces of the base substrate. A method for producing paper with so-called windowed threads can be found in EP-A-0059056. EP-A-0880298 and WO-A-03095188 describe different methods for embedding a wider partially exposed thread into a paper substrate. Wide threads typically having a width of 2 to 6 mm are particularly useful because the additional exposed thread surface area allows better use of optically variable devices. The security device or article may then be incorporated into a paper or polymer base substrate so that it is visible from both sides of the finished security substrate. Methods of incorporating security elements in this manner are described in EP-A-1 141480 and WO-A-03054297. In the method described in EP-A-1 141480, one side of the security element is fully exposed at one surface of the substrate where the security element portion is embedded, and is partially exposed in a window at the other surface of the substrate.
[0357] The base substrate suitable for making a security substrate for a security document can be formed of any conventional material, including paper and polymers. The technology for forming a substantially transparent area in each of these types of substrates is known in the art. For example, WO-A-8300659 describes a polymer banknote formed by a transparent substrate, which includes an opaque coating on both sides of the substrate. The opaque coating is omitted in the localized areas on both sides of the substrate to form a transparent area. In this case, the transparent substrate can be an integral part of the security device, or a separate security device can be applied to the transparent substrate of the document. WO-A-0039391 describes a method for making a transparent area in a paper substrate. Other methods for forming a transparent area in a paper substrate are described in EP-A-72350, EP-A-724519, WO-A-03054297 and EP-A-1398174.
[0358] The security device may also be applied to one side of the paper substrate so that the plurality of parts are located in openings formed in the paper substrate. An example of a method of producing such an opening can be found in WO-A-03054297. An alternative method of incorporating a security element (which is visible in the opening) in an opening on one side of the paper substrate and being fully exposed on the other side of the paper substrate can be found in WO-A-2000 / 39391.
[0359] Typically, secure products include banknotes, credit cards, identity documents (like passports, ID cards, driver's licenses) or other authentication documents, pharmaceutical packaging, software, compact discs, tobacco packaging and other products or packaging that are easily counterfeited or forged.
[0360] The substrate may comprise any sheet material. The substrate may be opaque, substantially transparent or translucent, wherein the method described in WO08 / 061930 is particularly suitable for substrates that are opaque to UV light (non-transparent). The substrate may comprise paper, leather, fabric such as silk, cotton, tyvac, film material or metal such as aluminium. The substrate may be in the form of one or more sheets or rolls.
[0361] The substrate may be molded, woven, nonwoven, cast, calendered, blown, extruded and / or biaxially extruded. The substrate may include paper, fabric, man-made fibers and polymer compounds. The substrate may include any one or more selected from the group consisting of paper, paper and board made from wood pulp or cotton or synthetic wood-free fibers. The paper / board may be coated, calendered or machine glazed; coated, uncoated, molded with cotton or denim content, Tyvac, linen, cotton, silk, leather, polyethylene terephthalate, polypropylene propafilm, polyvinyl chloride, rigid PVC, cellulose, triacetate, acetate polystyrene, polyethylene, nylon, acrylic and polyetherimide sheets. The polyethylene terephthalate substrate may be a Melinex-type film oriented polypropylene (available from DuPont Films Willimgton Delaware, product ID Melinex HS-2).
[0362] The substrate is a transparent film or a non-transparent substrate like opaque plastic, paper (including but not limited to banknotes, vouchers, passports and any other security or trust documents), self-adhesive stamps and excise seals, cards, tobacco, medicines, computer software packaging and certifications, aluminum, etc.
[0363] In a preferred embodiment of the invention, the substrate is a non-transparent (opaque) sheet material, such as paper. Advantageously, the paper can be pre-coated with a UV-curable lacquer. For example, WO 2015 / 049262 and WO 2016 / 156286 describe suitable UV-curable lacquers and coating methods.
[0364] In another preferred embodiment of the present invention, the substrate is a transparent or translucent sheet, such as polyethylene terephthalate, polyethylene naphthalate, polyvinyl butyral, polyvinyl chloride, flexible polyvinyl chloride, polymethyl methacrylate, poly(ethylene-co-vinyl acetate), polycarbonate, cellulose triacetate, polyether sulfone, polyester, polyamide, polyolefin such as polypropylene and acrylic resin. Among them, polyethylene terephthalate and polypropylene are preferred. The flexible substrate is preferably biaxially oriented.
[0365] Forming an optically variable image on a substrate can include depositing a curable composition on at least a portion of the substrate, as described above. The curable composition (usually a coating or lacquer) can be deposited by gravure printing, flexographic printing, inkjet and screen printing. The curable lacquer can be cured by actinic radiation, preferably ultraviolet (UV) light or electron beam. Preferably, the curable lacquer is UV-cured. UV-curable lacquers are well known and can be obtained from, for example, BASF SE. The lacquers used in the present invention that are exposed to actinic radiation or electron beams need to reach a curing stage when they are separated from the imaging pad again so that the record is maintained in the submicroscopic holographic diffraction grating image or pattern (optically variable image, OVI) of their upper layer. Particularly suitable for lacquer compositions are mixtures of typical well-known components (such as photoinitiators, monomers, oligomers, leveling agents, etc.) used in the field of radiation-curable industrial coatings and plates. Particularly suitable are compositions containing one or more photo-potential catalysts that will initiate the polymerization of the lacquer layer exposed to actinic radiation. Particularly suitable for rapid curing and conversion to the solid state are compositions comprising one or more monomers and oligomers sensitive to free radical polymerization, such as acrylates, methacrylates or monomers and / or oligomers containing at least one ethylenically unsaturated group, examples of which have been given above. Further reference is made to pages 8 to 35 of WO 2008 / 061930.
[0366] UV paint can contain Epoxy monomers of the Sartomer Europe range (10% to 60%) and one or more acrylates (monofunctional and polyfunctional) (monomers available from Sartomer Europe) (20% to 90%) and one or more photoinitiators (1% to 15%) such as 1173 and leveling agents such as BYK Chemie 361 (0.01% to 1%). UV paint can also be used for external coating.
[0367] The epoxy monomer is selected from aromatic glycidyl ethers and aliphatic glycidyl ethers. Aromatic glycidyl ethers are, for example, bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol B diglycidyl ether, bisphenol S diglycidyl ether, hydroquinone diglycidyl ether, alkylation products of phenol / dicyclopentadiene, such as 2,5-bis[(2,3-epoxypropoxy)phenyl]octahydro-4,7-methano-5H-indene (CAS No. [13446-85-0]), tris[4-(2,3-epoxypropoxy)phenyl]methane isomers (CAS No. [66072-39-7]), phenol-based epoxy novolacs (CAS No. [9003-35-4]) and cresol-based epoxy novolacs (CAS No. [37382-79-9]). Examples of the aliphatic glycidyl ethers include 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, 1,1,2,2-tetrakis[4-(2,3-epoxypropoxy)phenyl]ethane (CAS No. [27043-37-4]), diglycidyl ether of polypropylene glycol (α,ω-bis(2,3-epoxypropoxy)poly(oxypropylene), CAS No. [16096-30-3]), and diglycidyl ether of hydrogenated bisphenol A (2,2-bis[4-(2,3-epoxypropoxy)cyclohexyl]propane, CAS No. [13410-58-7]).
[0368] The one or more acrylates are preferably selected from the following multifunctional monomers: trimethylolpropane triacrylate, trimethylolethane triacrylate, trimethylolpropane trimethacrylate, trimethylolethane trimethacrylate, tetramethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol diacrylate, tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), pentaerythritol diacrylate, pentaerythritol tripropylene glycol ... acrylate, pentaerythritol tetraacrylate, dipentaerythritol diacrylate, dipentaerythritol triacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, tripentaerythritol octaacrylate, pentaerythritol dimethacrylate, pentaerythritol trimethacrylate, dipentaerythritol dimethacrylate, dipentaerythritol tetramethacrylate, tripentaerythritol octamethacrylate, pentaerythritol diitaconate, dipentaerythritol tripentaconate Acid esters, dipentaerythritol pentaitaconate, dipentaerythritol hexaitaconate, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol diitaconate, sorbitol triacrylate, sorbitol tetraacrylate, pentaerythritol modified triacrylate, sorbitol tetramethacrylate, sorbitol pentaacrylate, sorbitol hexaacrylate, oligoester acrylates and oligoester methacrylates, glycerol diacrylate and glycerol triacrylate, 1,4-cyclohexane diacrylate, diacrylates and dimethacrylates of polyethylene glycols having a molecular weight of 200 to 1500, triacrylates of mono- to twenty-fold alkoxylated, more preferably mono- to twenty-fold ethoxylated trimethylolpropane, mono- to twenty-fold propoxylated glycerol or mono- to twenty-fold ethoxylated and / or propoxylated pentaerythritol, such as, for example, ethoxylated trimethylolpropane triacrylate (TMEOPTA), and or mixtures thereof.
[0369] The photoinitiator may be a single compound or a mixture of compounds. Examples of photoinitiators are known to the person skilled in the art and are disclosed, for example, by Kurt Dietliker in "A compilation of photoinitiatorscommercially available for UV today", SitaTechnology Textbook, Edinburgh, London, 2002.
[0370] The photoinitiator may be selected from acylphosphine oxide compounds, benzophenone compounds, α-hydroxyketone compounds, α-alkoxyketone compounds, α-aminoketone compounds, phenylglyoxylate compounds, oxime ester compounds, mixtures thereof, and mixtures and mixtures thereof.
[0371] The photoinitiator is preferably a blend of an α-hydroxy ketone, α-alkoxy ketone or α-amino ketone compound and a benzophenone compound; or a blend of an α-hydroxy ketone, α-alkoxy ketone or α-amino ketone compound, a benzophenone compound and an acylphosphine oxide compound.
[0372] The curable composition is preferably deposited by gravure printing or flexographic printing.The curable composition may be pigmented.
[0373] The OVD is cast onto the surface of a curable composition using a gasket having an OVD thereon, imparting a holographic image into the lacquer and curing immediately via UV lamp to become a replica of the OVD disposed on the gasket (US 4,913,858, US 5,164,227, WO 2005 / 051675 and WO 2008 / 061930).
[0374] The curable coating composition according to the present invention can be applied to the OVD by conventional printing presses such as gravure, inkjet, rotogravure, flexographic, lithographic, offset, letterpress and / or screen printing, or other printing processes.
[0375] Preferably, the HRI layer printed on the OVD is also thin enough to allow viewing in transmission and reflection. In other words, the entire security element on the substrate allows viewing in transmission and reflection.
[0376] The curable composition may further comprise modifying additives.
[0377] Specific additives can be added to the composition to change its chemical properties and / or physical characteristics. Polychromatic effects can be achieved by introducing (colored) inorganic and / or organic pigments and / or solvent-soluble dyes into the ink to achieve a range of colored shades. By adding dyes, the transmission color can be affected. By adding fluorescent or phosphorescent materials, the transmission and / or reflected color can be affected.
[0378] Suitable colored pigments include, in particular, organic pigments selected from the group consisting of azo, azomethine, methine, anthraquinone, phthalocyanine, pyrenone, perylene, diketopyrrolopyrrole, thioindigo, dioxazine, iminoisoindoline, iminoisoindolinone, quinacridone, flavonoid, indanthrone, anthrapyrimidine and quinophthalone pigments, or mixtures or solid solutions thereof; in particular dioxazine, diketopyrrolopyrrole, quinacridone, phthalocyanine, indanthrone or iminoisoindolinone pigments, or mixtures or solid solutions thereof.
[0379] Colored organic pigments of particular interest include CI Pigment Red 202, CI Pigment Red 122, CI Pigment Red 179, CI Pigment Red 170, CI Pigment Red 144, CI Pigment Red 177, CI Pigment Red 254, CI Pigment Red 255, CI Pigment Red 264, CI Pigment Brown 23, CI Pigment Yellow 109, CI Pigment Yellow 110, CI Pigment Yellow 147, CI Pigment Orange 61, CI Pigment Orange 71, CI Pigment Orange 73, CI Pigment Orange 48, CI Pigment Orange 49, CI Pigment Blue 15, CI Pigment Blue 60, CI Pigment Violet 23, CI Pigment Violet 37, CI Pigment Violet 19, CI Pigment Green 7, CI Pigment Green 36, 2,9-dichloro-quinacridone in flake form as described in WO 08 / 055807, or mixtures or solid solutions thereof.
[0380] Flake-form organic pigments such as flake-form quinacridones, phthalocyanines, fluororubbers, dioxazines, red perylenes or diketopyrrolopyrroles can be advantageously used.
[0381] Suitable colored pigments also include conventional inorganic pigments; in particular those selected from the group consisting of metal oxides, antimony yellow, lead chromate, lead chromate sulfate, lead molybdate, ultramarine blue, cobalt blue, manganese blue, chromium oxide green, hydrated chromium oxide green, cobalt green and metal sulfides such as cerium sulfide or cadmium sulfide, cadmium sulfoselenide, zinc ferrite, bismuth vanadate, Prussian blue, Fe3O4, carbon black and mixed metal oxides.
[0382] Examples of dyes that can be used to color the curable composition are selected from the group consisting of azo, azomethine, methine, anthraquinone, phthalocyanine, dioxazine, flavonol, indanthrone, anthrapyrimidine and metal complex dyes. Monoazo dyes, cobalt complex dyes, chromium complex dyes, anthraquinone dyes and copper phthalocyanine dyes are preferred.
[0383] The surface relief micro- and nanostructures are, for example, microlens arrays, micromirror arrays, optically variable devices (OVDs), which are, for example, diffractive optically variable images (DOVIs). The term "diffractive optically variable image" as used herein may refer to any type of hologram, including, for example, but not limited to, multi-plane holograms (e.g., 2-dimensional holograms, 3-dimensional holograms, etc.), stereograms, and grating images (e.g., dot matrices, pixel maps, sample maps, dynamic maps, etc.).
[0384] Examples of optically variable devices are holograms or diffraction gratings, moiré gratings, lenses, etc. These optical micro- and nanostructured devices (or images) consist of a series of structured surfaces. These surfaces can have straight or curved profiles with constant or random spacing, and the size can even vary from microns to millimeters. The pattern can be circular, linear, or have no uniform pattern. For example, a Fresnel lens has a micro- and nanostructured surface on one side and a planar surface on the other side. The micro- and nanostructured surface consists of a series of grooves with varying tilt angles as the distance from the optical axis increases. The transition facets (draft facets) located between the tilted facets generally do not affect the optical performance of the Fresnel lens.
[0385] A further aspect of the invention is the use of an element as described above for preventing counterfeiting or copying on a document of value, right, identity, security label or branded merchandise.
[0386] The composition comprising metal oxide nanoparticles of the invention can be applied on top of transparent windows, security threads and surface relief micro- and nanostructures in foils on documents of value, rights, identity, security labels or branded goods.
[0387] The coating of the present invention can be used in the method for manufacturing the security device described in EP 2951023A1, which method comprises:
[0388] (a) providing a transparent substrate,
[0389] (b) applying a curable transparent material to an area of the substrate;
[0390] (c) partially curing the curable transparent material by exposure to curing energy in a first curing step;
[0391] (d) applying a layer of the coating of the present invention (reflection enhancing material) onto the curable transparent material;
[0392] (e) forming a layer of partially cured transparent material and coating composition such that both surfaces of the layer of coating of the invention follow the contours of the optically variable effect producing the relief structure,
[0393] (f) In a second curing step, the formed transparent material is completely cured by exposure to curing energy, so that the relief structure is maintained by the formed transparent material.
[0394] The various aspects and features of the present invention will be further discussed based on examples.The following examples are intended to illustrate various aspects and features of the present invention.
[0395] The various aspects and features of the present invention will be further discussed based on examples.The following examples are intended to illustrate various aspects and features of the present invention.
[0396] Examples
[0397] Measurement of pH of dispersions in ethanol
[0398] An aliquot of the nanoparticle dispersion in ethanol was mixed with deionized water (1:1 v / v) under vigorous stirring, and the pH in the resulting mixture was measured by a pH meter.
[0399] Measuring the Refractive Index of Coatings by Ellipsometry
[0400] The formulation was spin-coated onto a polished silicon wafer, the solvent was evaporated by air dryer at 100°C for 0.5 min, and the product was heated with a medium pressure Hg lamp at 500 mJ / cm 2 The dry coating was irradiated with a total UV dose of 1000 nm to obtain a coating with a thickness of at least 140 nm (thickness measured with a KLA Tencor Alpha-Step D-100 Stylus Profiler). Data were acquired using a Woollam M-2000-R19 ellipsometer (589 nm) in reflection mode at 65°, 70°, and 75° angles, and the data obtained were fitted using a Cauchy model with WVase32 software.
[0401] Particle size distribution measurement by DLS
[0402] The measurements were performed using a Malvern Zetasizer Nano ZS apparatus with a dispersion of approximately 3% w / w nanoparticles in a suitable solvent. The measurements in ethanol were performed in the presence of acrylic acid (15% w / w acrylic acid was added relative to the particle weight). The measurements in water were performed in the presence of 1 mM HCl. The D10, D50 and D90 values are given for the volume distribution.
[0403] Solids content measurement
[0404] The solids content of powders and dispersions (with cyclopentanone for dispersions) was determined using a Mettler-Toledo HR-73 halogen moisture analyzer at 105°C or 130°C.
[0405] Determination of the total amount of volatile surface modification compounds
[0406] In a thermogravimetric analysis using a TGA / DSC 3+ thermogravimetric analyzer from Mettler-Toledo, the total amount of volatile surface-modifying compounds in the dispersion after the neutralization step is determined as the weight loss in the range of 200°C-600°C relative to the residue at 600°C, provided that the highest boiling point solvent in the composition has a boiling point below about 170°C. About 20 to 40 mg of the dispersion sample is filled in a peeled aluminum crucible, immediately sealed to avoid weight loss before the experiment and weighed. The exact mass of the sample is recorded. The aluminum crucible is placed in a TGA oven at 30°C. The crucible lid is pierced at the same time. The heating rate is 10°C / min and the measurement is completed in a nitrogen flow in the range of 30°C to 600°C.
[0407] XRD measurement
[0408] The powder sample is loaded onto a special flat silicon sample holder, with special attention paid to producing a flat and smooth surface that is correctly aligned with respect to the sample holder zero reference to avoid large systematic errors. The silicon sample holder is manufactured so that it does not produce sharp diffraction features but only a weak and smooth background.
[0409] The sample on the sample holder was loaded into Panalytical'XPert3Powder equipped with a sealed Cu tube and the wavelength I2 / I1=0.5 and The characteristic X-ray line Cu K is generated under α and CuK β . Removal of the latter (Cu K β ) contribution, thereby introducing a Ni filter on the incident beam of the diffractometer immediately after the Cu tube.
[0410] Diffraction data were collected from 10 to 80° 2Θ using a step size of 0.026° 2Θ for a total time of 2 h, and the sample was rotated about its axis at a rate of 0.13 rate / sec in order to increase the sampling statistics.
[0411] Diffraction pattern analysis for crystallographic phase analysis and average domain size was performed using Panalytical HighScore software (v 4.8+) and Bruker Topas6 program, obtaining consistent results.
[0412] The volume-weighted domain size (Dv) of the diffraction was evaluated using the Scherrer equation (BE Warren, X-ray Diffraction, Addison-Wesley Publishing Co., 1969) Dv = Kλ / [βcos(θ)], where K (about 1) is the shape factor, depending on the shape and reciprocal space direction, λ is the wavelength, β is the integrated width of the diffraction peak, and θ is the scattering half-angle. To ensure the correct determination of Dv, a correction was made for the integrated width β of the instrumental contribution. To achieve this, the line broadening of the powder reference material LaB6 was measured and evaluated according to the same procedure as described above.
[0413] Evaluation of the lightfastness of coatings.
[0414] The light fastness of the coatings was evaluated using a filtered xenon lamp on a WOMCI 65 apparatus from ATLAS according to test method DIN EN ISO 105-B02 using the following parameters:
[0415] - Lighting intensity: [E] 1.1W / m at 420nm 2 ,
[0416] - Filters: CIRA - internal filter and soda lime - external filter
[0417] Plus filter lamp made of glass according to DIN 572-4
[0418] The transmission of the filter should be at least 90% between 380 and 750 nm and drop to zero between 310 and 320 nm.
[0419] -Relative humidity 50±5%
[0420] -Temperature during exposure 30±5℃
[0421] - Black panel temperature 45±5℃
[0422] The test is performed as follows:
[0423] The samples and blue wool scale were exposed to light for 120 h.
[0424] Determine which blue wool reference has changed to the same extent as the test piece. Give the test piece a lightfastness rating corresponding to the number of blue wool references that have changed to approximately the same extent as the test piece.
[0425] Rating:
[0426] 1 Very bad 2 Difference 3 medium 4 Relatively good 5 good 6 very good 7 Excellent 8 outstanding
[0427] Synthesis Example 1 (see PCT / EP 2021 / 072873 (WO 2022 / 038161))
[0428] Step 1. Synthesis of TiO2 nanoparticles
[0429] All operations were carried out under a dry nitrogen atmosphere. 1-Methoxy-2-propanol (1060 g) was placed in a 2L double-walled reactor equipped with a mechanical stirrer and a reflux condenser at room temperature. Titanium tetraisopropoxide (454.4 g) was added in one go, and the temperature was raised to 34 ° C. The mixture was cooled to 25 ° C and stirred for 1 h. A mixture of water (58.2 g) and 37% w / w hydrochloric acid (90.8 g) was then added in one go with stirring, and the temperature was raised to about 40 ° C. The reaction mixture was heated from 40 ° C to 85 ° C in 90 min and stirred at this temperature for 4 h.
[0430] The reaction mixture was cooled to 25°C and filtered through filter paper (20 μm pore size) under vacuum. The product was washed on the filter with anhydrous ethanol (800 g) and slightly dried on the filter for 2 min. An off-white powder of TiO2 nanoparticle agglomerates (179.5 g) was obtained. The solid content at 100°C was 64.4% w / w. XRD analysis showed that anatase was the main phase with a crystalline domain size of 3.7±0.9 nm. D10(v)=2.5 nm, D50(v)=3.8 nm, D90(v)=7.4 nm (in 1 mM HCl in water).
[0431] Step 2. Neutralization / redispersion of TiO2 nanoparticles
[0432] The powder obtained in step 1 (169.3 g) was resuspended in absolute ethanol (377 g). The temperature of the mixture was raised to 75° C., acetylacetone (6.54 g) was added and the pH of the mixture was brought to 5.5 by dropwise addition of a freshly prepared solution of potassium methoxide (23% w / w) in absolute ethanol (60.38 ml) at 75° C. with stirring. Upon addition of the potassium methoxide solution, the turbidity of the mixture was greatly reduced due to the redispersion of the TiO2 nanoparticle agglomerates. The mixture was cooled to 25° C. and filtered through a depth filter disc (Filtrox AF ST130) at 2.5 bar pressure to remove the potassium chloride formed together with traces of non-redispersed TiO2 nanoparticles. The pale yellow filtrate (552.0 g) containing the redispersed TiO2 nanoparticles was collected. The solids content at 100° C. was 18.9% w / w. D10(v) = 2.3 nm, D50(v) = 3.1 nm, D90(v) = 7.6 nm (in ethanol in the presence of acrylic acid). The total amount of volatile surface modification compounds as determined by thermogravimetric analysis (weight loss in the range of 200°C-600°C relative to the residue at 600°C) was found to be 18.0%; the residue at 600°C was found to be 15.5%, based on the total weight of the dispersion.
[0433] Application Example 1
[0434] Formulations were prepared, coatings were coated and the refractive index of the coatings was measured.
[0435] A. Trithiocyanuric acid (0.945 g) was added to 100 g of the dispersion obtained in Step 2 of Synthesis Example 1, the mixture was stirred for 30 min under an argon atmosphere and then diluted with 278 g of anhydrous ethanol.
[0436] B. Cyclopentanone (40 g) was added to 100 g of the dispersion obtained in step 2 of Synthesis Example 1, and the mixture was concentrated on a rotary evaporator at a pressure of 70 mbar and a bath temperature of 35° C. to a solid content of 30% (measured at 130° C.). Trithiocyanuric acid (2.84 g) and pentaerythritol tetraacrylate (4.24 g) were added, and the mixture was stirred under an argon atmosphere for 30 minutes.
[0437] Substrate preparation
[0438] PET foil (Melinex 506) was coated with a clear UV-curable varnish (Lumogen OVD 311, commercially available from BASF) using a wired K-type manual coater #1 and a medium-pressure mercury UV lamp (total UV dose of about 350 mJ / cm 2 ) The coating thus obtained is cured.
[0439] Preparation of coatings containing TiO2 nanoparticles and trithiocyanuric acid
[0440] Formulation A prepared in Application Example 1 was coated onto the thus prepared substrate using a wired K-type manual coater #0 (approximately 4 μm wet coating thickness), dried with an air dryer at 80° C. for 10 seconds and illuminated with a medium pressure mercury UV lamp (total UV dose of approximately 500 mJ / cm 2 ) to obtain a cured coating A. The coating was placed in an ambient atmosphere and allowed to stand at room temperature for 72 h.
[0441] Formulation B prepared in Application Example 1 was coated onto the thus prepared substrate using a wired K-type manual coater #2 (about 12 μm wet coating thickness), dried with an air dryer at 100° C. for 30 seconds and exposed to light using a medium pressure mercury UV lamp (total UV dose about 500 mJ / cm 2 ) to obtain a cured coating B. The coating was allowed to stand at room temperature under ambient atmosphere for 72 h.
[0442] Refractive index measurement.
[0443] The refractive index of the coatings obtained with formulations A and B was measured as described above. The data obtained are presented in Table 1.
[0444] Table 1. Thickness and refractive index measurements.
[0445] Cured coating thickness, nm Refractive index at 589nm Preparation A 150±7 2.013 Preparation B 226±5 1.861
[0446] Evaluate the chemical resistance properties and mechanical stability of coatings
[0447] Chemical resistance was evaluated by immersing the coated foil after UV curing and 72h post-curing period in anhydrous ethanol, a solution of 20% w / w acetic acid in water, 100% acetic acid, a solution of 5% w / w NaOH in water or a solution of 5% HCl in water for 30 minutes at room temperature. Afterwards, the foil was rinsed with deionized water and dried in an air dryer at room temperature. The dry foil was visually assessed (observation of reflected color and defects in the coating caused by interference) using a gray scale annotation of 0 to 4 (0 - coating completely disappeared, 1 - major changes; more than 50% damaged, 2 - significant changes; less than 50% damaged, 3 - minor changes, 4 - coating unchanged) compared to the untreated reference.
[0448] The mechanical stability of the coating was evaluated by manually rubbing the coating once with a nylon glove and visually rating the behavior using a notation of 0 or 1 (0 - white marks on the coating, 1 - no change in the coating).
[0449] For lightfastness evaluation, a wired K-type manual coater #1 was used to coat the surfaces with a clear UV-curable varnish ( OVD 311, commercially available from BASF) was coated with a cured coating (about 6 μm wet coating thickness) obtained from formulations A and B as described above, and a medium-pressure mercury UV lamp (total UV dose of about 350 mJ / cm 2 ) The coating thus obtained is cured.
[0450] Table 2. Chemical and mechanical resistance tests
[0451] Coating A Coating B Ethanol 4 4 Acetic acid, 20% w / w in water 4 3 Acetic acid 4 3 HCl, 5% w / w in water 0 3 NaOH, 5% w / w in water 4 2 Mechanical stability 1 1 Lightfastness >6 5-6
Claims
1. A coating composition, especially a UV-Vis curable coating composition, comprising i) single or mixed metal oxide nanoparticles, wherein the volume average diameter (D v 50) in the range of 1 to 20 nm, ii) one or more monomers having at least three thiol groups (—SH) at the terminal ends (first monomers), iii) optionally one or more monomers having at least two functional groups at the terminal ends capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer), iv) one or more solvents.
2. The coating composition according to claim 1, wherein The first monomer is of formula of the compound (trithiocyanuric acid).
3. The coating composition according to claim 1 or 2, wherein The second monomer is selected from bis(4-methacryloylthienyl) sulfide, dipropylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate, octanediol diacrylate, octanediol dimethacrylate Acid esters, nonanediol diacrylate, nonanediol dimethacrylate, decanediol diacrylate, decanediol dimethacrylate, cyclohexanediol diacrylate, cyclohexanediol dimethacrylate, cyclohexanedimethanol diacrylate, cyclohexanedimethanol dimethacrylate, (ethoxylated) neopentyl glycol diacrylate, (propoxylated) neopentyl glycol diacrylate, (ethoxylated) neopentyl glycol dimethacrylate, (propoxylated) neopentyl glycol dimethacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane trimethacrylate, ethoxylated glycerol triacrylate, ethoxylated glycerol trimethacrylate, propoxylated glycerol triacrylate, propoxylated glycerol trimethacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, ethoxylated ditrimethylolpropane tetraacrylate, propoxylated ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, propoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetramethacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, propoxylated dipentaerythritol hexaacrylate, and mixtures thereof.
4. The coating composition according to any one of claims 1 to 3, wherein The solvent is selected from C2-C4 alcohols, especially ethanol, 1-propanol and isopropanol; ketones, especially acetone, 2-butanone, 2-pentanone, 3-pentanone, cyclopentanone and cyclohexanone; ether alcohols, especially 1-methoxy-2-propanol; mixtures thereof and mixtures thereof with esters, especially ethyl acetate, 1-propyl acetate, isopropyl acetate and butyl acetate.
5. The coating composition according to any one of claims 1 to 4, wherein The single or mixed metal oxide nanoparticles are titanium dioxide nanoparticles, and the volume average diameter (D v 50) is in the range of 1 to 10 nm, preferably 1 to 5 nm.
6. The coating composition according to any one of claims 1 to 5, wherein The nanoparticles contain at least one volatile surface-modifying compound selected from ethanol and acetylacetone and mixtures thereof, wherein the total amount of volatile surface-modifying compounds is in the range of 10 to 50% by weight, in particular 10 to 40% by weight, very particularly 15 to 35% by weight, based on the amount of metal oxide nanoparticles.
7. The coating composition according to any one of claims 1 to 6, wherein The single or mixed metal oxide nanoparticles are titanium dioxide nanoparticles and are obtained by a process comprising the following steps: a) preparing a mixture comprising a compound of formula Ti(OR 12 )4(Xa) metal alkoxide, solvent, HCl and water, wherein R 12 is C1-C4 alkyl, preferably methyl, ethyl, n-propyl, isopropyl and n-butyl; b1) heating the mixture to a temperature of 80° C. to 100° C.; b2) separating the obtained TiO2 nanoparticles from the mixture; b3) resuspending the TiO2 nanoparticles in a C1-C4 alcohol or a mixture of C1-C4 alcohols; b4) optionally treating the TiO2 nanoparticles with one or more β-diketones or one or more salts thereof; c1) treating the TiO2 nanoparticles with a base; c2) optionally treating the TiO2 nanoparticles with one or more β-diketones or one or more salts thereof; c3) optionally with the formula Me'(OR 20 ') z (VII) or a mixture thereof to treat the TiO2 nanoparticles; and c4) filtering the mixture to obtain a dispersion of TiO2 nanoparticles, wherein R 20 ' is a C1-C8 alkyl group, preferably a C1-C4 alkyl group; Me' is selected from Zn(II), In(III), Sc(III), Y(III), La(III), Ce(IV), Ti(III), Ti(IV), Zr(IV), Hf(IV), Sn(IV), V(IV), Nb(V) and Ta(V), preferably Ti(IV), Zr(IV), Sn(IV), Nb(V) and Ta(V); and z is equal to the oxidation state of the metal; where The solvent comprises at least one ether group and one alcohol group; The ratio of the number of moles of water to the total number of moles of Me and Me' is in the range of 3:1 to 5:1, more preferably 3.2:1 to 4.5:1, especially 3.5:1 to 4.5:1; The ratio of moles of HCl to moles of titanium is in the range of 1:1 to 0.3:1, preferably 0.8:1 to 0.35:1, especially 0.7:1 to 0.4:
1.
8. The coating composition according to any one of claims 1 to 7, comprising, based on the total weight of one or more components i), ii), iii) and iv). i) 3 to 50% by weight of said single or mixed metal oxide nanoparticles, ii) 0.15 to 10% by weight of one or more monomers having a triazine ring and at least three thiol groups (—SH) at the terminal ends (first monomer), iii) 0 to 30% by weight of one or more monomers having at least two functional groups at the terminals capable of reacting with a thiol group and a spacer group between the at least two functional groups (second monomer), and iv) 20 to 96.9% by weight of one or more solvents.
9. A coating having a refractive index of greater than 1.7, in particular greater than 1.8, very particularly greater than 1.9, obtainable from a coating composition according to any one of claims 1 to 8.
10. The coating according to claim 9, which has a thickness of 0.01 to 0.50 microns, preferably 0.02 to 0.40 microns, more preferably 0.03 to 0.30 microns, most preferably 0.04 to 0.25 microns after drying and UV curing; or the coating according to claim 9, which has a thickness of 0.10 to 30.0 microns, preferably 0.20 to 20.0 microns, more preferably 0.30 to 10 microns, most preferably 0.50 to 6.0 microns after drying and UV curing.
11. A method for forming a coating having a high refractive index on a substrate, the method comprising the steps of: a) providing a substrate, preferably with a surface relief nano- and / or micro-structure; b) applying the coating composition according to any one of claims 1 to 8 to the substrate by wet coating or printing; c) removing the solvent; as well as d) exposing the dry coating to actinic radiation, especially UV light.
12. A security or decorative element comprising a substrate which may include indicia or other visible features in or on its surface; and a coating according to claim 9 or 10, or a coating obtained according to the method of claim 11, on at least a portion of the surface of the substrate.
13. A method for forming a surface relief micro- and nanostructure on a substrate, the method comprising the following steps: a) forming surface relief micro- and / or nanostructures on discrete portions of the substrate; b) depositing a coating composition according to any one of claims 1 to 8 on at least a portion of the surface relief micro- and / or nanostructure; c) removing the solvent; as well as d) curing the dry coating by exposing the dry coating to actinic radiation, especially UV light; or A method for forming a surface relief micro- and / or nanostructure on a substrate, the method comprising the following steps: a') providing a substrate sheet, the sheet having an upper surface and a lower surface; b') depositing a coating composition according to any one of claims 1 to 8 on at least a portion of the upper surface; c') removing the solvent; d') forming a surface relief micro- and / or nanostructure on at least a portion of the coating composition; e') curing the dry coating obtained in step d') by exposing it to actinic radiation, in particular UV light; or A method for forming a surface relief micro- and / or nanostructure on a substrate, the method comprising the following steps: a'') providing a substrate sheet, the sheet having an upper surface and a lower surface; b'') depositing a coating composition according to any one of claims 1 to 8 on at least a portion of the upper surface; c'') removing the solvent; d'') forming a surface relief micro- and / or nanostructure on at least a portion of the coating composition, such that the micro- or nanostructure is at least partially formed in the substrate; e'') curing the dry coating obtained in step d") by exposing it to actinic radiation, especially UV light.
14. The method according to claim 13, wherein: Step a) comprises a1) applying a curable compound to at least a portion of the substrate; a2) contacting at least a portion of the curable compound with a surface relief micro- and nanostructure forming device; as well as a3) curing the curable compound.
15. Use of the coating composition according to any one of claims 1 to 8 for coating diffractive optical elements (DOEs), holograms, making optical waveguides and solar panels, light outcoupling layers for display and lighting devices, high dielectric constant (high-k) gate oxides and interlayer high-k dielectrics, anti-reflective coatings, etch and CMP stop layers, optical thin film color filters, optical diffraction gratings and hybrid thin film diffraction grating structures, high refractive index wear resistant coatings - in protection and sealing (OLED), or organic solar cells.
Citation Information
Patent Citations
Use of nanoparticles and / or organosilanes for the production of prestressed, multilayer coated glass substrates
DE102010009999A1
Method for making a fibrous sheet
EP0059056A1
A protecting device for information visible on part of a watch case
EP0072350A1
Paper, in particular security paper
EP0724519A1
Packet switching system, network and method
EP0880298A2